A New Model for Inclusive Sports? An Evaluation of Participants’ Experiences of Mixed Ability Rugby - Corazza, Martino (2017)
Sport has been recognised as a potential catalyst for social inclusion. The Mixed Ability Model represents an innovative approach to inclusive sport by encouraging disabled and non-disabled players to interact in a mainstream club environment. However, research around the impacts of the Model is currently lacking. This paper aims to contribute empirical data to this gap by evaluating participants’ experiences of Mixed Ability Rugby and highlighting implications for future initiatives. Primary qualitative data were collected within two Mixed Ability Rugby teams in the UK and Italy through online questionnaires and focus groups. Data were analysed using Simplican et al.’s (2015) model of social inclusion. Data show that Mixed Ability Rugby has significant potential for achieving inclusionary outcomes. Positive social impacts, reported by all participants, regardless of (dis)ability, include enhanced social networks, an increase in social capital, personal development and fundamental perception shifts. Factors relevant to the Mixed Ability Model are identified that enhance these impacts and inclusionary outcomes. The mainstream setting was reportedly the most important, with further aspects including a supportive club environment and promotion of self-advocacy. A ‘Wheel of Inclusion’ is developed that provides a useful basis for evaluating current inclusive sport initiatives and for designing new ones.